Comparative study of ultrasound application versus mechanical agitation on pork belly brining for bacon production - Ribeiro-Sanches, Marcio Augusto [UNESP]; Martins, Maria Júlia Neves [UNESP]; Borges-Machado, André Luiz [UNESP]; de Almeida, Micael José [UNESP]; Fonseca, Bruna Grassetti [UNESP]; Polachini, Tiago Carregari [UNESP]; Telis-Romero, Javier [UNESP] (Elsevier, 2024)
Pork belly brining is a time-consuming step of bacon production that needs to be studied and enhanced through suitable technologies. In this sense, this study aimed at evaluating the impact of ultrasound (US), mechanical agitation (AG), and static brine (SB) on the kinetics of water loss (WL), solids gain (SG), and salt content (SC) of pork belly during brining under different temperatures. Mathematical models were used to estimate mass transfer rates, equilibrium parameters, and thermodynamic properties. Peleg model was chosen as the most suitable model to predict the kinetics experimental data (Radj2 ≥ 0.979 and RMSE ≤ 0.014). The increase in the brine temperature increased WL, SG, and SC for all treatments. Nonlinear effects of temperature were observed for WL, SG, and SC, following an Arrhenius-type behavior. The assistance of ultrasound significantly enhanced the velocity of WL, SG, and SC by 32–56%, while AG improved by 18–39% both compared to SB. Brining was considered an endothermic and non-spontaneous process through the thermodynamic assessment. The increase in temperature and the AG and US processes accelerated the formation of the activated complex. The application of ultrasound was considered the most suitable technology to reduce the brining time. However, significant improvements can be obtained by mechanical agitation. Therefore, both methods can be used to reduce the time processing of pork belly aiming at accelerating the bacon production process.
Keywords: Emerging technologies; Kinetics mathematical modeling; Mass transfer; Meat brining; Thermodynamics